2011
DOI: 10.1007/s00253-011-3387-z
|View full text |Cite
|
Sign up to set email alerts
|

The viability to a wall shear stress and propagation of Bifidobacterium longum in the intensive membrane bioreactor

Abstract: Bifidobacterium longum grew at 65 L pilot scale of the membrane bioreactor (MBR), externally fitted with ceramic membrane (0.7 m2). Cell mass at the MBR reached 22.18 g L(-1) as dry cell weight in 12 h, which is 8.44 times higher than cell mass attained at the vial culture. The growth rate in the vial culture was μ = 0.385 h- and at the batch culture was μ = 1.13 h- in the exponential period and μ = 0.31 h(-1) in the stationary period. In the fed-batch mode was μ = 1.102 h(-1) for 6 h with inoculation and decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…High cell-density cultures and the cell size control for manufacturing of MHT-LM1004 were conducted under shear stress conditions, controlling the pump speed and the flow rate of the cell culture fluids in the MBR (15-L pilot scale, anaerobic conditions with N 2 gas), which was externally fitted with the ceramic membrane (5.7-m 2 effective area, 0.2-μm pore size, Pall Corporation, USA) and the centrifugal pump (Grundfos, Denmark). The wall shear stress, which is one of the crucial factors for altering the morphology of L. plantarum LM1004, was generated while the cells were passing through the hydraulic channels of the ceramic membrane and the centrifugal pump [13,14]. After intensive propagation in the MBR, the cells were killed at 80°C for 20 min (Ultra High Temperature, Sam-Ryung Sterilization Co, Korea), washed through the ultrafiltration membrane (effective area of 1.2 m 2 , 0.1-μm pore size, Pall Corporation) three times with reverse osmosis (RO) water, and freeze dried.…”
Section: Preparation Of Mht-lm1004mentioning
confidence: 99%
“…High cell-density cultures and the cell size control for manufacturing of MHT-LM1004 were conducted under shear stress conditions, controlling the pump speed and the flow rate of the cell culture fluids in the MBR (15-L pilot scale, anaerobic conditions with N 2 gas), which was externally fitted with the ceramic membrane (5.7-m 2 effective area, 0.2-μm pore size, Pall Corporation, USA) and the centrifugal pump (Grundfos, Denmark). The wall shear stress, which is one of the crucial factors for altering the morphology of L. plantarum LM1004, was generated while the cells were passing through the hydraulic channels of the ceramic membrane and the centrifugal pump [13,14]. After intensive propagation in the MBR, the cells were killed at 80°C for 20 min (Ultra High Temperature, Sam-Ryung Sterilization Co, Korea), washed through the ultrafiltration membrane (effective area of 1.2 m 2 , 0.1-μm pore size, Pall Corporation) three times with reverse osmosis (RO) water, and freeze dried.…”
Section: Preparation Of Mht-lm1004mentioning
confidence: 99%
“…Kwon et al (2006) reported seven times higher concentrations of B. bifidum, compared to batch cultures, when using a submerged membrane bioreactor. Similarly, Jung et al (2011) also reported higher cell yields using a membrane reactor as opposed to free cell fermentation of B. longum. In a membrane system with a constant feeding of fresh medium, the bacteria are kept in the bioreactor by an ultrafiltration or microfiltration membrane.…”
Section: Fermentation Technologiesmentioning
confidence: 86%
“…During fermentation, mechanical stress originates from mixing and hydrostatic pressure changes, and during downstream processing, cells are exposed to mechanical stress from pumping, centrifugation, or membrane filtration (252). Wall shear stress in a membrane bioreactor was shown to affect the viability of B. longum severely (253). Moreover, bifidobacteria are exposed to mechanical stress during preservation and in food manufacturing processes (2,254,255).…”
Section: Mechanical Stressmentioning
confidence: 99%